Cover Image, Volume 179A, Number 7, July 2019. Issue 7 (10th June 2019) - Gucev, Zoran; Tasic, Velibor; Plaseska‐Karanfilska, Dijana; Dimishkovska, Marija; Laban, Nevenka; Bozinovski, Zoran; Kostovski, Marko; Saveski, Alek; Polenakovic, Momir; Towler, O. Will; Shore, Eileen M.; Kaplan, Frederick S.
Abstract : The cover image is based on the Clinical Report Severe digital malformations in a rare variant of fibrodysplasia ossificans progressive by Zoran Gucev et al., DOI:10.1002/ajmg.a.61153 .